Effects of different protein levels and selenium supplementation on reproductive performance and quality of fresh, chilled and post-thawed semen of dorper ram - Mohd Razaki, Julie Marzlinda (2018)
Consumption of mutton products in this country is increasing, yet the population of sheep are decreasing. As reported by the Department of Veterinary Services, numbers of live sheep been imported into this country increased by 48% in 2016. In addition, selfsuffiency of mutton products of this country had decreased by 8.05% since 2012.Dorper sheep known for its high potential in meat production was imported to this country as an alternative breed to help increase the meat livestock industry. Several studies were done on the performance of Dorper breed in Malaysia but there are still lack of information on ram reproductive performance influence by local feed and environment. The objective of this study was to evaluate the effects of two different crude protein (CP) levels and Selenium (Se) supplementation on reproductive performances and semen quality of Dorper rams. In a 2 x2 factorial design, diets used were180 g of CP (PL) or 270 g (PH) and each group were supplemented with organic Se (S1) at 1 mg/kg of body weight or without (S0) supplementation. Energy was maintained at 12.5 MJ ME/kg DM and feeding trial were carried out for 140 days. Dietary treatments were formulated which consisted 50% mix concentrate and 50% untreated rice straw as fibre source. During feeding trials, average daily feed intake (ADFI), total weight gain (TWG) and average daily gain (ADG) of rams were determined. Blood samples were collected once every 28 days to determine testosterone and Se concentration in blood serum. Libido or time reactions of first mount were observed. Semen was collected using an artificial vagina (AV) and fresh semen was evaluated. Sperm motion and morphometric were observed using CEROS. Semen with more than 70% of motility was used to cryopreserve and assessment were carried out after 4 hr cooling at 4°C and post-thawed. Eosin-nigrosin stain was used to determined sperm viability and abnormalities while, Pope's stain was used to evaluate sperm acrosome integrity. Hypo-osmotic swelling test (HOST) was used to determined membrane integrity of sperm. In this study, there were no interactions between CP and Se in all parameters except for libido and testosterone concentration. Therefore, all parameters are shown according to the main effects. Libido and testosterone concentration were presented according to the interaction and correlation between both parameters were analysed. As a result, neither protein nor Se supplement influenced TWG, ADFI, ADG and Se concentration in blood serum of Dorper rams. However, there was an interaction (p<0.05) between both CP and Se on libido and testosterone concentration. Combination of PLS0 had the best time reaction (8.56±1.45 sec) on mounting and the highest testosterone concentration (4.19±0.25 ng/ml) in blood serum. Nevertheless, there was no correlation between libido and testosterone yet an inverse relationship (r = -0.20) was observed. In this study, CP levels did not affect volume, semen concentration and viability. In contrast, PL showed a significant increment (p<0.05) on wave motion. Meanwhile, S1 showed higher (p<0.05) wave motion but significantly decreased (p<0.05) semen volume. Nonetheless, Se showed no effect on semen concentration and viability. Neither CP nor Se improved sperm motion and morphometric except where S1 showed higher (p<0.05) percentage of total motility compared to S0. In sperm morphology, CP and Se treatment also showed no significant effect sperm normality, abnormalities of head, midpiece and tail, membrane and acrosome integrity of fresh semen except where S1 showed higher (p<0.05) percentage of acrosome integrity than S0. Varying CP level and Se supplementation, showed no significant effect on all parameters of chilled semen. In post-thawed semen, rams fed with different level of CP and Se showed no effect on sperm motions and morphometric, viability and morphology except where S1 showed increased in amplitude lateral head (ALH) (p<0.05) and had significantly lower (p<0.05) percentage of sperm head abnormality as compared to S0. This study concluded that feeding higher levels of CP do not improve reproductive performance or semen quality. PL produce better performance in fresh semen and supplementation of organic Se did enhance the quality of fresh and post-thawed semen. Higher dosage of organic Se is suggested for further studies to observe the potential in improving reproductive parameters of Dorper rams.